Islamic Elementary School Marketing Model in Pekanbaru: The Impact of Digitalization of Education - Sakban Sakban; Muhammad Lisman; Susi Marni; Wismanto (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
Elementary Schools play a strategic role in educating Human Resources (HR). Therefore, proper governance is the keyword for sustainability for Institutions, both State and Private. The emergence of the era of disruption is a test of every governance of educational and non-educational institutions. Adaptation to technological developments is the only solution for the legitimacy of institutional sustainability. The gap in digital marketing research in elementary schools and the absence of a role model for the concept of a digital marketing model for elementary schools make this research very strategic at this time, especially in the city of Pekanbaru which has many private elementary schools. Analysis of the research journal matrix using Vosviewer accessed through the Elsevier Scopus journal and Google Schooler digital marketing or digitalization for elementary school management is research that has been the focus of researchers to date and has many opportunities to be used as research studies that show that this research is part of what will fill the research gap. The purpose of this study is to reveal how digital technology influences Integrated Islamic Elementary Schools (SD IT), especially in the field of school marketing. Analyze opportunities and challenges and find a digital marketing model for elementary schools. This study uses a qualitative method using the Notions Of Sensing And Responding theory. So the findings of this study are that the development of digital technology has changed the promotion model that leads to digital marketing. This is reinforced by the school's response and the initiatives taken by the school in adopting and developing digital marketing.